Pengelolaan Pembelajaran Siswa Cerdas Dan Berbakat Istimewa Di Sd Negeri No. 16 Surakarta - Gestoni H., Fery (2016)
The objectives of the research are to know and describe: 1) the identification processes of gifted students; 2) the learning plan, organization, actuation, and evaluation of the gifted students; and 3) the supporting and inhibiting factors of gifted students' learning management at SD Negeri Nomor 16 Mangkubumen Kecamatan Laweyan Kota Surakarta. The type of the research is a qualitative research. The design of the researh is ethnographical design. The research was undertaken at SD Negeri Nomor 16 Mangkubumen Kecamatan Laweyan Kota Surakarta. The object of the research was the gifted students' learning management at SD Negeri Nomor 16 Mangkubumen Kecamatan Laweyan Kota Surakarta. The data collecting method is done using observation, in-depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The research concludes that: 1) the gifted students' identification processes is done through a series of processes, namely: test and interview. The test undertaken comprises of academic, psychological, and medical tests, and interview with both the students and their parents. The identification processes were done in cooperation with Psychological Institution namely Lembaga Psikologi Anava of Surakarta; 2) the planning process was initiated by the curriculum design, syllable, and lesson plan construction. The curriculum employed is differentiated curriculum. The learning facilities provided to facilitate the gifted students' learning is specifically managed by empowering the school's environment and the available school's facilities; and 3) The supporting factors in learning management for the gifted students involving: 1) the adequate support from the stake holders; 2) the non-material support provided by the stake holder cover the various activities of the parents organization to support the school program and the networking. The inhibiting factor in learning management for the gifted students involving the lack of special teacher to handle them. The lack of teacher who handles these students were solved by providing special conselor of Psychologist from Lembaga Psikologi Anava Surakarta.